Eight years of Doha trade talks: Where do we stand? - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2010)
In 2001, the World Trade Organization launched a highly ambitious program of multilateral liberalization. Eight years later, concluding the negotiations is uncertain, though an opportunity still exists. Since 2001, many proposals on market access have been brought to the negotiating table by the E.U., the United States, and the G-20. Because it is politically and economically acceptable to many parties, the final December 2008 package could be the basis of an agreement. An evaluation of these various proposals shows how trade negotiations have been following countries' strategic interests. In eight years, the ambition of the formula to reduce agricultural market access tariffs has increased, but flexibilities added to accommodate domestic political constraints have offset delivered market access. The December 2008 package would reduce these average tariffs by 25 percent, a reduction very close to the one implied by the Harbinson and Girard proposals of 2003. This has to be compared with the 73 percent reduction in world agricultural protection by the very ambitious 2005 U.S. proposal. The 2005 G-20 and E.U. proposals were intermediate outcomes. The December 2008 package implies a reduction of agricultural protection by 6 percentage points in high-income countries and 0.5 percentage points in middle-income countries. If the U.S. proposal had been applied, these figures would have been 12.4 and 4.7, respectively. Different scenarios imply losses for developing countries, reflecting eroding preferences and rising terms of trade for imported commodities, including food products. We study how this trade reform can be more development-friendly.